Views of Implementers and Nonimplementers of Internet-Administered Cognitive Behavioral Therapy for Depression and Anxiety: Survey of Primary Care Decision Makers in Sweden - Brantnell, Anders; Woodford, Joanne; Baraldi, Enrico; van Achterberg, Theo; von Essen, Louise (JMIR Publications, 2020)
BackgroundInternet-administered cognitive behavioral therapy (ICBT) has been demonstrated to be an effective intervention for adults with depression and/or anxiety and is recommended in national guidelines for provision within Swedish primary care. However, the number and type of organizations that have implemented ICBT within primary care in Sweden is currently unclear. Further, there is a lack of knowledge concerning barriers and facilitators to ICBT implementation. ObjectiveThe two primary objectives were to identify and describe primary care organizations providing ICBT in Sweden and compare decision makers' (ie, directors of primary care organizations) views on barriers and facilitators to implementation of ICBT among ICBT implementers (ie, organizations that offered ICBT) and nonimplementers (ie, organizations that did not offer ICBT). MethodsAn online survey based on a checklist for identifying barriers and facilitators to implementation was developed and made accessible to decision makers from all primary care organizations in Sweden. The survey consisted of background questions (eg, provision of ICBT and number of persons working with ICBT) and barriers and facilitators relating to the following categories: users, therapists, ICBT programs, organizations, and wider society. ResultsThe participation rate was 35.75% (404/1130). The majority (250/404, 61.8%) of participants were health care center directors and had backgrounds in nursing. Altogether, 89.8% (363/404) of the participating organizations provided CBT. A minority (83/404, 20.5%) of organizations offered ICBT. Most professionals delivering ICBT were psychologists (67/83, 80%) and social workers (31/83, 37%). The majority (61/83, 73%) of organizations had 1 to 2 persons delivering ICBT interventions. The number of patients treated with ICBT during the last 12 months was 1 to 10 in 65% (54/83) of the organizations, ranging between 1 and 400 treated patients across the whole sample. There were 9 significant (P<.05) differences out of 37 possible between implementers and nonimplementers. For example, more implementers (48/51, 94%) than nonimplementers (107/139, 76.9%) perceived few technical problems (P<.001), and more implementers (53/77, 68%) than nonimplementers (103/215, 47.9%) considered that their organization has resources to offer ICBT programs (P<.001). ConclusionsDespite research demonstrating the effectiveness of ICBT for depression and anxiety and national guidelines recommending its use, ICBT is implemented in few primary care organizations in Sweden. Several interesting differences between implementers and nonimplementers were identified, which may help inform interventions focusing on facilitating the implementation of ICBT.